2020
DOI: 10.1108/bfj-07-2019-0476
|View full text |Cite
|
Sign up to set email alerts
|

Craft beer mon amour: an exploration of Italian craft consumers

Abstract: Purpose The purpose of this paper is to contribute understanding tendencies of the Italian demand for craft beer. More in details, it seeks at exploring consumers’ awareness about craft beer, their attitudes, habits and behaviors. It also aims at assessing the impact of each and all these features on consumers’ choice. At last, the paper frames different consumers’ profiles. Design/methodology/approach The analysis is based on an online survey associated with a choice experiment designed for assessing willin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 34 publications
4
28
1
Order By: Relevance
“…The number of breweries and beer brands globally has expanded dramatically in recent decades (Garavaglia and Swinnen 2018 ). Consumers are also demanding higher product quality and beer with novel and diverse flavours (Aquilani et al 2015 ; Carbone and Quici 2020 ; Gonzalez Viejo and Fuentes 2020 ). As much of beer flavour is yeast-derived (Holt et al 2019 ), brewers may meet this demand and keep ahead of competition by diversifying their products through the use of different yeast strains.…”
Section: Introductionmentioning
confidence: 99%
“…The number of breweries and beer brands globally has expanded dramatically in recent decades (Garavaglia and Swinnen 2018 ). Consumers are also demanding higher product quality and beer with novel and diverse flavours (Aquilani et al 2015 ; Carbone and Quici 2020 ; Gonzalez Viejo and Fuentes 2020 ). As much of beer flavour is yeast-derived (Holt et al 2019 ), brewers may meet this demand and keep ahead of competition by diversifying their products through the use of different yeast strains.…”
Section: Introductionmentioning
confidence: 99%
“…Interest towards beer with novel and diverse flavours is increasing (Aquilani et al, 2015;Carbone and Quici, 2020;Gonzalez Viejo and Fuentes, 2020), and the results here suggest that hybridization and subsequent sporulation can give rise to lager yeast strains with both enhanced and diverse production of aroma-active compounds. 3-methylbutyl acetate, with its banana-and pear-like aroma, is one of the most important yeast-derived flavor compounds in beer (Pires et al, 2014).…”
Section: Aroma Diversitymentioning
confidence: 73%
“…Creating new flavour profiles, e.g. in response to the increased consumer demand for higher product quality and beer with novel and diverse flavours (Aquilani et al, 2015; Carbone and Quici, 2020; Gonzalez Viejo and Fuentes, 2020), is hampered by the low level of diversity amongst commercial brewing yeast strains. Previous research has shown that interspecific hybridization is an effective way of introducing new aromatic diversity among lager yeasts (Krogerus et al, 2015; Mertens et al, 2015; Nikulin et al, 2018; Turgeon et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Interest toward beer with novel and diverse flavors is increasing (Aquilani et al, 2015;Carbone and Quici, 2020;Gonzalez Viejo and Fuentes, 2020), and the results here suggest that hybridization and subsequent sporulation can give rise to lager yeast strains with both enhanced and diverse production of aroma-active compounds. 3-methylbutyl acetate, with its banana-and pear-like aroma, is one of the most important yeastderived flavor compounds in beer (Pires et al, 2014).…”
Section: Aroma Diversitymentioning
confidence: 74%